THE RELATIONSHIP BETWEEN THE DECISION-MAKING PROCESS AND ACHIEVEMENT MOTIVATION AMONG THE HIGH SCHOOL STUDENTS INVOLVED IN TEAM BUILDING ACTIVITIES WITHIN PHYSICAL EDUCATION AND SPORT CLASSES - TANASĂ, Anca-Raluca; ABALAȘEI, Aurelia-Beatrice; DUMITRU, Iulian-Marius (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Introduction: The integration of team building activities into Physical Education and Sports classes represents an essential tool for the socioemotional and motivational development of young people within the school environment. Objective: The objective of this research study was to analyse the relationship between emotion-based decision-making and achievement motivation among high schoolers participating in team building activities integrated into Physical Education and Sports classes. Material and Methods: The study involved 50 high school students, both female and male. By administering two questionnaires from the field of personality assessment (“Emotion-Based Decision-Making” and “Achievement Motivation”), meant to analyse emotion-based decision-making and achievement motivation, we evaluated the relationship between these two dimensions. To obtain the representation of the association between them, we used Pearson’s correlation coefficient. We performed data processing and statistical analysis using SPSS software, version 20. Results: We found a significant positive correlation between emotion-based decision-making and achievement motivation among students (r = 0.453, DF = 48, p < 0.001). Our findings indicate that students participating in team building activities during School Physical Education classes display a decision-making process influenced by emotional factors and prove a strong desire for achievement. This aspect highlights a correlation between the emotional side of decision-making and individual motivation. Consequently, a higher degree of emotional involvement in decision-making correlates with increased individual motivation for achievement and personal satisfaction. Discussion: To underscore similarities and differences, the findings of this research study were compared with data from the literature addressing the relationship between emotions and the educational process in school physical activities, as reported, for instance, in the study titled “Emotions–Decision-Making in Sport: Theoretical Conceptualization and Experimental Evidence” published by Gershon Tenenbaum, Itay Basevitch, Lael Gershgoren, and Edson Filho in 2013. Conclusions: The research study has demonstrated that team building activities play an essential role in developing the socio-emotional competencies of high school students, thus allowing a better management of emotions in the decision-making process and supporting their motivation for achievement.